Zur Genitalmorphologie und Systematik der neotropischen Spezies des Elminthidae-Genus Microcylloepus Hinton, 1935 (Coleoptera: Dryopoidea). - Bug, Konrad (Contributions to Entomology = Beiträge zur Entomologie, 1973)
Different neotropic species of the genus Microcylloepus Hinton, 1935 of the Elminthidae were examined of the genitalmorphological aspects and systematic placed. The characteristics of genus which were studied by Hinton (1940c), were re-examinned. The diagnosis of the genus was more precisely examined. The micromorphological structure of the genitalia of eight neotropic Microcylloepus species was examined and for new species described: Microcylloepus acuminatus sp. n., Microcylloepus pumilus sp. n., Microcylloepus steffani sp. n., Microcylloepus latus sp. n. Probable relationships are discussed. The study of the morphology of the examined species and of the morphology of the genitalia shows that groups of species exist within the genus Microcylloepus Hinton, 1935. The dependence of the size of the body on the biocoenosis of the examined species could not be determined for the lack of ecological data. Hinton's assertion that the male genitalia of various species of the genus Microcylloepus Hinton, 1935 are identical could not be confirmed by the present investigation. The M. immsi group differs distinctly from all other species of Microcylloepus Hinton, 1935 in habitus.Nomenclatural Actsacuminatus Bug, 1973 (Microcylloepus), spec. n.latus Bug, 1973 (Microcylloepus), spec. n.pumilus Bug, 1973 (Microcylloepus), spec. n.steffani Bug, 1973 (Microcylloepus), spec. n.